The Influence of Social Learning on Flight Operation Officer Competency Mediated by Emotional Intelligence: A Study at the Akademi Penerbang Indonesia Banyuwangi - Rochmad Setiawan; Dede Ardian (Education Policy and Development, 2025)
The aviation industry requires highly competent Flight Operations Officers (FOOs) for safe and efficient operations. This study explores the relationships between Social Learning, Emotional Intelligence (EI), and FOO competencies using Social Learning Theory (SLT) and emphasizing observation and experiential learning. Competencies include technical and non-technical skills, such as judgment and teamwork, which are vital for high-pressure aviation environments. This research examines SLT processes, EI levels, and FOO competencies among 72 students at the Akademi Penerbang Indonesia (API) Banyuwangi, determining the direct and indirect influences of Social Learning on competencies through EI. Data were collected using structured questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results revealed that social learning significantly impacted EI and competencies (p < 0.05), with EI acting as both a direct and mediating factor. Students with higher EI demonstrated enhanced decision-making, problem-solving, and interpersonal collaboration, which are key to FOO roles. Findings suggest integrating EI-focused training, including simulations, role-playing, and feedback mechanisms, into FOO curricula to strengthen core competencies. This study contributes to aviation education by building on Bandura’s and Goleman’s theories, emphasizing how SLT and EI integration can better prepare students for real-world aviation challenges. By highlighting these elements’ importance, the research advocates for balanced technical and nontechnical training in future aviation education programs.